A Restarting Strategy for Back-EMF-Based Sensorless Permanent Magnet Synchronous Machine Drive - Zih-Cing You (Energies, 2019)
Safely starting a spinning position sensorless controlled permanent magnet synchronous machine is difficult because the current controller does not include information regarding the motor position and speed for suppressing the back-electromotive force (EMF)-induced current. This paper presents a restarting strategy for back-EMF-based sensorless drives. In the proposed strategy, the existing back-EMF and position estimator are used and no additional algorithm or specific voltage vector injection is required. During the restarting period, the current controller is set to a particular state so that the back-EMF estimator can rapidly estimate motor voltage without using rotor position and speed. Then, this voltage is used to decouple the back-EMF of the motor in the current controller in order to suppress the induced current. After the back-EMF is decoupled from the current controller, sensorless control can be restored with the estimated position and speed. The experimental results indicated that the induced current can be suppressed within four to five sampling periods regardless of the spinning conditions. Because of the considerably short time delay, the motor drive can restart safely from various speeds and positions without causing overcurrent fault.